2019
DOI: 10.1016/j.pcad.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A role for FNDC5/Irisin in the beneficial effects of exercise on the brain and in neurodegenerative diseases

Abstract: The beneficial effects of exercise on the brain are well known. However, the underlying molecular mechanisms are much less well understood. Interestingly, myokine, hormones secreted by muscle in response to exercise, gained attention as such beneficial mediators. In this review, we will focus on FNDC5 and its secreted form, the newly discovered myokine "irisin". We will discuss their role in the beneficial effects of exercise and its potential application in neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 73 publications
(91 reference statements)
1
68
0
1
Order By: Relevance
“…FNDC5 was recognized as a transmembrane protein with a bronectin III domain and a carboxy-terminal domain located in the cytoplasm (35) . Irisin is the extracellular domain of FNDC5, which is cleaved by enzyme (14,36) .…”
Section: Discussionmentioning
confidence: 99%
“…FNDC5 was recognized as a transmembrane protein with a bronectin III domain and a carboxy-terminal domain located in the cytoplasm (35) . Irisin is the extracellular domain of FNDC5, which is cleaved by enzyme (14,36) .…”
Section: Discussionmentioning
confidence: 99%
“…For all these reasons, irisin is considered a critical myokine related to body metabolism. Moreover, increasing evidence proposes irisin also as a mediator of the beneficial effects of exercise on the brain function (memory) and in neurodegenerative diseases …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing evidence proposes irisin also as a mediator of the beneficial effects of exercise on the brain function (memory) and in neurodegenerative diseases. [13][14][15] Although it was demonstrated that irisin expression is detectable around the paraventricular nucleus region in human hypothalamic sections where it colocalizes with NPY, 16 the potential role of irisin in the regulation of body weight and food intake is still unclear. Indeed, irisin administration has been shown to promote weight loss in diabetic mice or rats, [17][18][19][20][21][22] but other studies showed no differences in body weight between diabetic mice receiving irisin or not.…”
mentioning
confidence: 99%
“…FNDC5 was recognized as a transmembrane protein with a fibronectin III domain and a carboxyterminal domain located in the cytoplasm (27) . Once FNDC5 could be cleaved by an unknown enzyme, and the extracellular domain of FNDC5 was named as irisin (12,28) .…”
Section: Discussionmentioning
confidence: 99%